2021
DOI: 10.21203/rs.3.rs-345973/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexual Wellbeing in Early Adolescence: A Cross-sectional Assessment Among Girls and Boys in Urban Indonesia

Abstract: Background: Early adolescence (ages 10-14) is a critical period of physical, cognitive, social and emotional development, which affect sexual and reproductive health and rights. Yet, little is known about positive or healthy aspects of sexuality development during this period of life, especially in South East Asia where sexual norms remain restrictive. The objective of this study is to assess the prevalence and correlates of sexual wellbeing among early adolescent girls and boys ages in Indonesia.Methods: Data… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A recent scoping review concluded that young adolescents in low-and middle-income countries have inadequate SRHR knowledge, especially in terms of puberty and menstruation [40]. Young adolescents' SRHR knowledge in Rwanda is inadequate, as in many other settings such as Sub-Saharan Africa [30,41], Guangzhou City in China [42], Korea [43] and Indonesia [11]. The age of initiating sexuality education was another perceived determinant of access to SRHR information by young adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent scoping review concluded that young adolescents in low-and middle-income countries have inadequate SRHR knowledge, especially in terms of puberty and menstruation [40]. Young adolescents' SRHR knowledge in Rwanda is inadequate, as in many other settings such as Sub-Saharan Africa [30,41], Guangzhou City in China [42], Korea [43] and Indonesia [11]. The age of initiating sexuality education was another perceived determinant of access to SRHR information by young adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Early adolescence provides a window of opportunity to intensify the delivery of such SRHR information [9,10]. Through this socialisation process, young adolescents become significantly aware of their bodies, gender and sexuality [11]. Family members, media, and social institutions teach young adolescents appropriate behaviours [12,13] and norms for interacting, forming relationships, and engaging in social and sexual behaviours [14].…”
mentioning
confidence: 99%
See 2 more Smart Citations